Retrospection of Bhopal gas tragedy. Issue 9 (20th October 2016) - Mittal, Alok
Abstract : Almost 30 long years have been passed since the World's worst disastrous industrial tragedy at Bhopal but its havoc still upsets our memories and pains our heart. This article gives a detailed overview on the possible causes of the accident and state of affairs of the city on the ill-fated night of 2 December 1984. Since the article is incorporated in the special issue "Science, Responsibility and Governance, " attempts have been made to keep the subject matter of the article within the framework of the journal theme.